Tantangan dan Peluang Belajar Bahasa Arab dengan Pendekatan Behaviorisme dalam Era Digital - Alallah, Ikhlasul Amal (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Arabic is a very important language to learn and understand. The behaviorist approach is a new way of learning Arabic, along with other advantages that accompany technological advances in the digital era. Which emphasizes the role of reinforcement and stimulus-response in learning. However, using a behaviorist approach in learning Arabic has its own challenges in the digital era. The research objective of this article is to examine the opportunities and challenges of the behaviorist approach in learning Arabic in the digital era, where if it does not immediately adapt to the digital era, Arabic language education will be left behind and lose its relevance. By taking advantage of the opportunities offered by digital technology to improve the quality of Arabic language learning and prepare students for the future. The future of Arabic education depends on how we respond to the digital era. By using a library research approach, this research methodology allows for a literature-based examination of the relationship between behaviorism, Arabic language learning, and the digital era. The findings of the content analysis identify and analyze the need to modify the ideas of behaviorism theory to suit the dynamics of Arabic language learning in the digital era and the importance of integrating content, media, methodology and evaluation in a balanced way when teaching Arabic. In this situation, behaviorism methods combined with digital technology are expected to increase the effectiveness of Arabic language learning. Despite these obstacles, the development of an innovative Arabic language learning platform can open the door to increasing the effectiveness of the behaviorist approach in learning Arabic in the digital era. As a result, this article offers a comprehensive understanding of the challenges and opportunities of learning Arabic with a behaviorist approach in the digital era.